2016
DOI: 10.1038/ncomms13458
|View full text |Cite
|
Sign up to set email alerts
|

An elastic element in the protocadherin-15 tip link of the inner ear

Abstract: Tip link filaments convey force and gate inner-ear hair-cell transduction channels to mediate perception of sound and head movements. Cadherin-23 and protocadherin-15 form tip links through a calcium-dependent interaction of their extracellular domains made of multiple extracellular cadherin (EC) repeats. These repeats are structurally similar, but not identical in sequence, often featuring linkers with conserved calcium-binding sites that confer mechanical strength to them. Here we present the X-ray crystal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(82 citation statements)
references
References 79 publications
6
74
2
Order By: Relevance
“…It is still unclear whether the tip link contributes to the gating spring, or if the gating spring is provided by one or more molecules connected in series to the tip link. Earlier structural studies of Cdh23 and Pcdh15 have focused on the question of tertiary structural elasticity – whether force applied to Pcdh15 will result in protein extension without unfolding (Araya-Secchi et al, 2016; Powers et al, 2017; Sotomayor et al, 2010, 2012). In these studies, Sotomayor and coworkers have reported crystal structures for monomeric EC domain pairs or triples produced in E. coli , and computationally assessed the spring properties of these cis -monomeric ectodomain fragments using steered molecular dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is still unclear whether the tip link contributes to the gating spring, or if the gating spring is provided by one or more molecules connected in series to the tip link. Earlier structural studies of Cdh23 and Pcdh15 have focused on the question of tertiary structural elasticity – whether force applied to Pcdh15 will result in protein extension without unfolding (Araya-Secchi et al, 2016; Powers et al, 2017; Sotomayor et al, 2010, 2012). In these studies, Sotomayor and coworkers have reported crystal structures for monomeric EC domain pairs or triples produced in E. coli , and computationally assessed the spring properties of these cis -monomeric ectodomain fragments using steered molecular dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In silico simulation of monomeric protein fragments encompassing the EC1 and EC2 domains of Cdh23 was reported to suggest that tip links might be too stiff to function as the gating spring, a hypothesis that was initially based on the observed double-stranded nature of the tip link (Kachar et al, 2000; Sotomayor et al, 2010). However, subsequent studies suggested that only some regions of the tip link might be too stiff to act as the gating spring, whereas other regions could potentially elongate significantly in response to force (Araya-Secchi et al, 2016; Powers et al, 2017; Sotomayor et al, 2012). These conclusions were based on crystal structures of Pcdh15 ectodomain fragments EC1-2, EC3-5, EC8-10, and EC9-10 (Araya-Secchi et al, 2016; Powers et al, 2017; Sotomayor et al, 2010, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations